IMPLIKASI TRANSFORMASI PERTANIAN MODERN KE ORGANIK TERHADAP PERBAIKAN KUALITAS LINGKUNGAN HIDUP - Yuliana, E. Dewi (Bumi Lestari; Vol 11 No 2 (2011), 2011)
This study was conducted to view the problem an the dark side of modern agriculture. The chemical substances used in agriculture have result ed in many problems such as the degradation on land quality, the continuous decrease of plant productivity and environment, as well the marginalization of farmers. Therefore, many farmers have been aware and have transformed their activities into ecologically organic agriculture such as at Subak Wangaya Betan. The farmers have transformed their technology from modern agriculture into organic agriculture. This research is designed by using method qualitative. Data type that is used in this research is data qualitative and supported by quantitative. Based on the conducted analysis, findings that could be reported. Included: First, employment of modern agriculture by using inorganic fertilizers and pesticides has been found to make a lower wetland soil quality. Second, by contrast, transformation of modern agriculture into organic agriculture causes soil quality improving. Third, beside, the improvement of soil quality employment of organic agriculture in the location where the study was performed also found that environment quality is improving.
Keywords: transformation agriculture; modern agriculture; organic agriculture; envirovement